Detailed phenotypic and functional characterization of CMV-associated adaptive NK cells in rhesus macaques - Hasan, Mohammad Zahidul; Höltermann, Charlotte; Petersen, Beatrix; Schrod, Annette; Mätz-Rensing, Kerstin; Kaul, Artur; Salinas, Gabriela; Dressel, Ralf; Walter, Lutz (Frontiers in Immunology, 2022)
Previous research on adaptive NK cells in rhesus macaques suffered from the lack of specific antibodies to differentiate between inhibitory CD94/NKG2A and stimulatory CD94/NKG2C heterodimeric receptors. Recently we reported an expansion of NKG2C receptor-encoding genes in rhesus macaques, but their expression and functional role on primary NK cells remained unknown due to this deficit. Thus, we established monoclonal antibodies 4A8 and 7B1 which show identical specificities and bind to both NKG2C-1 and NKG2C-2 but neither react with NKG2C-3 nor NKG2A on transfected cells. Using a combination of 4A8 and Z199 antibodies in multicolor flow cytometry we detected broad expression (4-73%) of NKG2C-1 and/or NKG2C-2 (NKG2C-1/2) on primary NK cells in rhesus macaques from our breeding colony. Stratifying our data to CMV-positive and CMV-negative animals, we noticed a higher proportion (23-73%) of primary NK cells expressing NKG2C-1/2 in CMV+ as compared to CMV- macaques (4-5%). These NKG2C-1/2-positive NK cells in CMV+ macaques are characterized by lower expression of IL12RB2, ZBTB16, SH2D1B, but not FCER1G, as well as high expression of IFNG, indicating that antibody 4A8 detects CMV-associated adaptive NK cells. Single cell RNA seq data of 4A8-positive NK cells from a rhCMV-positive macaque demonstrated that a high proportion of these adaptive NK cells transcribe in addition to NKG2C-1 and NKG2C-2 also NKG2C-3, but interestingly NKG2A as well. Remarkably, in comparison to NKG2A, NKG2C-1 and in particular NKG2C-2 bind Mamu-E with higher avidity. Primary NK cells exposed to Mamu-E-expressing target cells displayed strong degranulation as well as IFN-gamma expression of 4A8+ adaptive NK cells from rhCMV+ animals. Thus, despite co-expression of inhibitory and stimulatory CD94/NKG2 receptors the higher number of different stimulatory NKG2C receptors and their higher binding avidity to Mamu-E outreach inhibitory signaling via NKG2A. These data demonstrate the evolutionary conservation of the CMV-driven development of NKG2C-positive adaptive NK cells with particular molecular signatures in primates and with changes in gene copy numbers and ligand-binding strength of NKG2C isotypes. Thus, rhesus macaques represent a suitable and valuable nonhuman primate animal model to study the CMV-NKG2C liaison in vivo.